Redes sobrenaturales de la Monarquía Católica: Las hermandades hispanoamericanas agregadas a la archicofradía de la Resurrección de la nación española en Roma (1579-1808) - Calvo Gómez, José Antonio (Cauriensia, 2023)
This historical research work tries to analyze one of the instruments that sustained the spiritual structure of the Catholic Monarchy during Modernity. On July 20, 1591, Gregory XIV raised the brotherhood of the Holy Resurrection, in Rome, into an arch-brotherhood. Among other prerogatives, he granted its officers the privilege of being able to add the other brotherhoods with this title in the different villages and cities of the Hispanic Monarchy. In addition, he authorized them to transmit to them the same spiritual graces, indulgences and immunities that they enjoyed by concession of the Roman pontiffs since its foundation, in 1579. In practice, the brotherhoods that joined the Roman arch-brotherhood, at least 118, from Manila to Mexico City, created a mystical network that strengthened the feeling of belonging to a multinational project, the Catholic Monarchy, that had two well-defined axes: the king, and the confession of Catholic and Roman faith.